Regeneração natural de um fragmento de cerrado degradado com a formação de pastagens de braquiária (Urochloa decumbens (Stapf) R. D. Webster) - Rissi, Mariana Ninno [UNESP] (2011)
The concepts degraded environment and disturbed environment were initially proposed based on the observation of such processes in forest fragments. Disturbed environments, when subjected to agents, can reestablish after the removal of the disturbing factor. However, when the action is more intense and there is no potential to return to conditions similar to the previous ones, the vegetation is considered degraded. The question is: Would the actions that make a forest degraded have the same consequence in cerrado fragments? The present study aims to analyze the composition of the regenerative community over one year in a cerrado fragment located in the Municipal Botanical Garden of Bauru City, São Paulo State, Brazil (JBMB); to provide data to understand the ecological processes involved in the natural regeneration of degraded cerrado areas and the chemical combat as a viable alternative or not to control alien plants; and to contribute to the knowledge of the cerrado flora in Bauru region. Thus, some questions were raised. How does natural regeneration of the woody vegetation of a degraded cerrado occur? Would the chemical combat against invasive alien plants change the development of cerrado plants? Is intervention in the control of those plants favorable? The study area was deforested by the action of settlers, who established there in 1997. In 2007 the area was endorsed to the Municipal Botanical Garden of Bauru City (JBMB). During this period, the native vegetation was substituted for pasture. By two years ago the place has been abandoned and the natural vegetation started to regenerate. To evaluate the natural regeneration potential of cerrado, a comparative floristic and phytosociological survey was carried out in three areas inside JBMB. The first area is inserted in a cerradão fragment, free of... (Complete abstract click electronic access below)